Should the Decisions of Institutional Review Boards Be Consistent?. Issue 4 (23rd July 2019) - Friesen, Phoebe; Yusof, Aimi Nadia Mohd; Sheehan, Mark
ABSTRACT: In response to increasing concerns regarding inconsistency in the decision‐making of institutional review boards (IRBs), we introduce the decision‐maker's dilemma, which arises when complex, normative decisions must be made regularly. Those faced with such decisions can either develop a process of algorithmic decision‐making, in which consistency is ensured but many morally relevant factors are excluded from the process, or embrace discretionary decision‐making, which makes space for morally relevant factors to shape decisions but leads to decisions that are inconsistent. Based on an exploration of similarities between systems of criminal sentencing and of research ethics review, we argue for a discretionary system of decision‐making, even though it leads to more inconsistency than does an algorithmic system. We conclude with a discussion of some safeguards that could improve consistency while still making space for discretion to enter IRBs' decision‐making processes.